Organic polymers for CO2 capture and conversion - Sharma, Eshita; Rana, Supriyanka; Sharma, Isha; Sati, Priyanka; Dhyani, Praveen (Elsevier, 2023)
The continuous emission of CO2 due to burning of coal causes several environmental problems such as change in weather and global warming across the globe. Hence, it has become essential to capture CO2 in the atmosphere to reduce its effect on global warming. Various advanced technologies have been employed by industries to lessen CO2 emission in air or capture CO2 from the air. CO2 adsorption is achieved by employing porous materials such as zeolites, metal–organic frameworks, porous organic polymers (POPs), carbonaceous materials, and microporous polymers. The major technologies for CO2 uptake include pre- and postcombustion capture, and oxy-fuel combustion capture. The properties of POPs, viz. versatility, high surface area, structural flexibility, and enhanced stability, make them preferable material of choice for next-generation CO2 capture in recent days. In this chapter, we will discuss high performance of porous organic materials for CO2 uptake and challenges in the development of porous materials with future approaches for sustainable CO2 capture.